Karakteristik Lesi dan Faktor-Faktor Pemicu Penderita Stomatitis Aftosa Rekuren pada Mahasiswa Profesi Kedokteran Gigi USU Tahun 2019-2020 - Aida Fadhilla Darwis; Dania Lailani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Recurrent Aphthous Stomatitis (RAS) is ulcer in the oral mucosa that occur repeatedly with unknown etiologic factors but varied trigger factors and lesion characteristics. The prevalence of RAS still high in community, however pain and the recurrence impact the quality of life both in oral activities and daily activities such as: avoided brushing teeth that it causes poor oral conditions, impaired mastication, swallowing, speaking, feeling uncomfortable, difficulty sleeping and reducing social interaction. The purpose of this study was to determine the frequency distribution of lesion characteristics and the triggering factors for patients with recurrent aphthous stomatitis in USU dental professional students in 2019-2020. This research is a survey study with a cross sectional design. The population is students of the dental profession at the University of North Sumatra in 2019-2020 with a total sample of 62 respondents who were used as research subjects. Measurement of SAR variables using the Recurrent Aphthous Stomatitis Diagnosis (RASDX) questionnaire. The research data was obtained by distributing online questionnaires in the form of a google form. Students who were most affected by SAR were female at 87.1%. The most common type of SAR found was minor at 95.2%, was in the labial mucosa by 72.6%, single ulcers of 95.2%), history of ulcer duration suffered by respondents was around 7-14 days 54.8%, multifactorial triggering factors are genetic, trauma and stress (30,6%) with the most common triggering factor was stress at 93.5%. The characteristics RAS in this research were minor type on the labial mucosa, a single of number and duration of 7-14 days. Based on the trigger factors, it can be concluded that the most common group of 3 multifactor (genetic, trauma and stress) which stress is the most common factors.